Employee Loyaty at the Job Training Center (BLK) Post Government Policy - Don Gusti Rao (Jurnal Riset Manajemen dan Bisnis, 2026)
Abstract. This study aims to analyze the impact of the government’s budget efficiency policy (Inpres No. 1 of 2025) on employee loyalty at the Center for Vocational and Productivity Training (BBPVP) and the Vocational and Productivity Training Center (BPVP), hereafter collectively referred to as BLK. It also seeks to identify the factors influencing employee loyalty and formulate strategies to sustain employee engagement amid budgetary constraints. Employing a qualitative research method with data and source triangulation techniques, the study involved nine informants from three BLKs: Medan, Kota Bekasi, and Sorong City. The findings reveal that the BLK’s core business continues to operate effectively despite budget efficiency measures. The factors affecting employee loyalty—compliance with regulations, task performance capability, willingness to cooperate, sense of belonging, and work attitude—remain relatively dynamic. The strategies to maintain employee engagement include optimizing internal resources, strengthening organizational communication, enhancing employee competencies, fostering partnerships with local governments and the business sector, and restructuring program planning and prioritization.